Geographic Distribution of a Large Mobile Element That Transfers Ampicillin and Vancomycin Resistance between Enterococcus faecium Strains - Hanrahan, Jennifer (American Society for Microbiology, 2000)
In several clonally unrelated VanB-type vancomycin-resistant Enterococcus faecium strains, we demonstrated a common physical relationship between pbp5 and Tn5382 as well as common mutations within pbp5. The majority of these strains transferred vancomycin and ampicillin resistance to E. faecium in vitro, suggesting the dissemination of similar transferable pbp5-vanB-containing mobile elements throughout the United States.